SAT0646 THE EMERGING ROLE OF IGG ANTI-HIGH-DENSITY LIPOPROTEINS ANTIBODIES AS NOVEL BIOMARKER FOR THROMBOTIC ARTERIAL EVENTS IN ANTIPHOSPHOLIPID SYNDROME PATIENTS. (June 2019) - Cecchi, Irene; Radin, Massimo; Rubini, Elena; Suárez, Ana; Roccatello, Dario; Sciascia, Savino; Rodríguez-Carrio, Javier
Abstract : Background: The mechanisms underlying thrombosis and cardiovascular disease (CVD) in antiphospholipid syndrome (APS) are not completely understood, but recent evidences have brought to light the existence of a complex interplay between traditional CV risk factors and disease-specific features, such as the presence of autoantibodies [1]. Recent studies have discovered the existence of a heterogeneous group of autoantibodies specifically directed against lipoproteins and their components [anti-high density lipoproteins antibodies (anti-HDL)]. Anti-HDL showed promising results in predicting the development of CVD, lipoprotein dysfunction and clinical outcomes in autoimmune conditions. Nevertheless, the association between anti-HDL and clinical features of APS remains unclear. Objectives: The aim the study was to evaluate the presence of IgG anti-HDL antibodies in a cohort of thrombotic APS patients and to investigate if these antibodies can discriminate between arterial and venous thrombosis. Methods: This cross-sectional study included 60 patients with persistent antiphospholipid antibodies (aPL) positivity that fulfilled the Sydney criteria for thrombotic APS (venous and/or arterial) [2], and 20 age- and sex-matched healthy donors (HDs). Clinical data were retrospectively collected. Serum levels of total IgG, IgG anti-HDL antibodies and complete aPL profile were assessed, including lupus anticoagulant, anti-cardiolipin, anti-β2glycoprotein I, and anti-phosphatidylserine/prothrombin both IgG and IgM antibodies. Results: 43 patients (72%) were primary APS and 17 patients (28%) had a concomitant diagnosis of systemic lupus erythematosus. Thirty APS patients (50%) presented previous arterial events and 37 (61%) venous events (7 patients experienced recurrent thrombotic events, both venous and arterial; the first event was taken as a reference for the analyses). The characteristics of the cohort are displayed in Table 1 . Higher levels of IgG anti-HDL were found in APS patients compared to HDs [mean 46 (±70) vs. 14 (±13) AU, respectively; p <0.001], even after correcting for total IgG levels [mean 13 (±16) vs. 4.6 (±5), respectively; p <0.001] (Figure 1.1 ). No association with traditional cardiovascular risk factors, except for smoking habit (p <0.0001) was found. No differences in anti-HDL levels were observed between patients with primary APS and those with a concomitant autoimmune disease (p >0.050). Patients who experienced at least one arterial event had significantly higher levels of anti-HDL antibodies when compared to patients with history of venous thrombosis [mean 53 (SD ±94) vs. mean 34 (SD ±29), respectively; p =0.046]. This difference became stronger when adjusting for total IgG levels [anti-HDL/IgG: mean 13.1 (SD ±16.7) vs. mean 9.5 (SD ±6.6); p =0.007] (Figure 1.2 ). In addition, patients tested positive for aPS/PT (IgG/IgM) antibodies had significantly higher levels of anti-HDL antibodies [mean 53.1 (SD ±81.1) vs. mean 20.7 (SD ±17.6), p =0.045]. The levels of IgG anti-HDL antibodies were not influenced by pharmacological treatments (all p >0.050). Conclusion: Our study demonstrates that thrombotic APS patients have higher levels of IgG anti-HDL antibodies, supporting the emerging role of these autoantibodies in APS setting. Moreover, our findings suggest that anti-HDL represent a promising tool for risk management and assessment and a potential biomarker for lipid dysfunction and arterial thrombotic events. References: [1] Meroni PL, et al. Pathogenesis of antiphospholipid syndrome: understanding the antibodies. Nat Rev Rheumatol 7:330–339 (2011). [2] Miyakis S, et al. International consensus statement on an update of the classification criteria for definite antiphospholipid syndrome (APS). J Thromb Haemost 4:295–306 (2006). Disclosure of Interests: None declared